The Effect of the Characteristics of Banking Information Systems in Improving Banking Performance (A field study on real estate banks on the Syrian coast) - تفاحه, حسن (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The aim of the research is to determine the role of the characteristics of banking information systems in improving banking performance in real estate bank branches in the Syrian coast. The researcher followed the descriptive and analytical approach in his study, and a set of methods, including relying on secondary data, and primary through a questionnaire that was developed through the researcher's access to the published literature, and the research community consisted of workers at the upper and middle management levels in the real estate bank branches, and then the SPSS program was relied upon as a tool for analysis Available data. The study found that the real estate bank does not achieve an increase in the size of the market share, and the bank’s management is not keen to provide information to workers that help them in their work at the time they need. The study recommended that the bank should achieve an increase in the size of the market share, by increasing interest in marketing information systems, and the bank’s management must be keen to provide information that helps workers in their work at the time they need, because it improves their performance and this is reflected in the performance The bank in general.